Influence of teacher collaboration on job satisfaction and student achievement - Reeves, Philip M.; Pun, Wik Hung; Chung, Kyung Sun (Teaching and Teacher Education, 2017)
Teacher collaboration consists of many types of activities and interactions. This quantitative study examines how the effects of collaboration differ according to both the type and frequency of collaborative activity. TIMSS data was analyzed to determine whether five indicators of collaboration predicted student achievement, teacher job satisfaction, and teacher confidence in Japan and the United States. Collaboration during lesson planning was a significant predictor of student achievement in the United States. Time spent visiting other classrooms corresponded to higher job satisfaction ratings in the United States. The results provide insight into the effectiveness of different collaborative activities in each nation.
Keywords: Comparative education; Mathematics education; Teacher collaboration